2017
DOI: 10.1128/msphere.00324-17
|View full text |Cite
|
Sign up to set email alerts
|

A Quorum-Sensing System That Regulates Streptococcus pneumoniae Biofilm Formation and Surface Polysaccharide Production

Abstract: Quorum sensing regulates bacterial social behaviors by production, secretion, and sensing of pheromones. In this study, we characterized a new quorum-sensing system of the Rgg/SHP class in S. pneumoniae D39. The system was found to directly induce the expression of a single gene cluster comprising the gene for the SHP pheromone and genes with putative functions in capsule synthesis. Capsule size, as measured by dextran exclusion, was increased by SHP exposure in R36A, an unencapsulated derivative of D39. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 77 publications
(124 reference statements)
5
70
0
Order By: Relevance
“…A recent study characterized a quorum-sensing Rgg/SHP system in S. pneumoniae that increases surface polysaccharide synthesis by upregulation of a site distinct from the original capsule locus (28). Considering the genetic similarities between the pathogenic S. pneumoniae and oral streptococci from the mitis group, this study addressed whether other such systems could be identified in these closely related oral species as well.…”
Section: Screening Of Rgg/shp Cell-to-cell Communication Systems In Omentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study characterized a quorum-sensing Rgg/SHP system in S. pneumoniae that increases surface polysaccharide synthesis by upregulation of a site distinct from the original capsule locus (28). Considering the genetic similarities between the pathogenic S. pneumoniae and oral streptococci from the mitis group, this study addressed whether other such systems could be identified in these closely related oral species as well.…”
Section: Screening Of Rgg/shp Cell-to-cell Communication Systems In Omentioning
confidence: 99%
“…The search was performed using the expanded Human Oral Microbiome Database (HOMD) (32), a curated and comprehensive database on the bacterial species present in the human aerodigestive tract. Entries of species belonging to the mitis group of streptococci were included in the search, with the only exclusion being S. pneumoniae since it was recently described (28). In total, we examined 15 strains of S. mitis, 1 strain of S. gordonii, 9 strains of S. oralis, 13 strains of S. sanguinis, and 7 strains of S. parasanguinis.…”
Section: Screening Of Rgg/shp Cell-to-cell Communication Systems In Omentioning
confidence: 99%
See 2 more Smart Citations
“…The Ami oligopeptide importer then internalizes the pheromones back into the cell, where they bind to and modulate the activity of Rgg-family regulators (12). Besides PCATs and bacteriocin production, Rgg/SHP systems have been found to regulate diverse processes such as carbohydrate utilization (15), tissue invasion (13, 16), capsule production (16, 17), and biofilm formation (17, 18). A related group of Rgg regulators, the ComRs, are associated with SHP-like pheromones called ComS or XIP (SigX-inducing peptide) and control competence activation in some streptococcal species (19, 20).…”
Section: Introductionmentioning
confidence: 99%